BARRACK OBAMA’S IDEOLOGIES IN HIS CAMPAIGN SPEECH AT COLORADO STATE UNIVERSITY - Zulianingrum, Ana (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
In finding the ideologies, the researcher uses CDA (Critical Discourse Analysis) as a tool. By using this way, three main steps were applied; these are text analysis, discourse practice, and socio-cultural practice. It found that in text analysis, there are 21 repetitions spoken by Obama in his campaign speech, 2 synonymies, 7 hyponymy, 4 metonymies, and 6 antonyms. In the level of discourse practice, in opening, it was found that there are three main regularities in speech; these are phatic expressions, emotive function, and thanking. In content, the regularities are the use of jargon, poetic expressions and directive expressions. And in closing, the regularities are sequenced first by uttering the supportive utterance, poetic expressions, and farewell greeting. The last step, socio-cultural practice, it is found that there are 9 direct responses, applause for 77 times, laughter for 12 times, and last response by sneezing appears for once. Going through those steps, the researcher can take three dominant ideologies uttered by Obama; they are “Forwarding United State is needed”, “No choice except choosing Obama”, and “Raising tax is improper to raise citizen’s prosperity”.